Analysis of benefits from being in a Alzheimer Internet support group for the caregivers of the people suffering from Alzheimer’s disease - Bartosz Grobelny; Małgorzata Awdziejczyk; Wojciech Gorczyński; Marcin Janczyk; Marta Leszczyńska; Katarzyna Meissner; Agnieszka Roszyk; Radosław Specjalski; Paulina Śniegula; Jolanta Tomczak; Katarzyna Wiecheć (Journal of Medical Science, 2014)
Both emotional and physical demands faced by Alzheimer's disease caregivers are very difficult to meet. Often, the amount of strength and calmness needed to fulfil the role of caregiver is beyond the person’s adaptability. The aim of this article is the data analysis of the Alzheimer’s disease caregivers online support groups and problems the caregivers face on the daily basis. Authors compared discussions and solutions available in polish language with methods used in other countries. The study was conducted in late April and May of 2013 by analyzing the user posts found on Polish webistes that associates the caregivers of people suffering form Alzheimer’s disease. Authors assumed that there is a difference between citizens of different countries in the access to useful information that may help in solving daily problems. Confirmation of this hypothesis may indicate the need for modifications by creating a professional platform that associates Alzheimer’s disease caregivers. Authors also analyzed remedies caregivers use and emotional functioning. By presenting recurring problems regarding diagnosis, burnout and coping with daily stress. They try to answer important question: what must be done to meet the needs of caregivers presented via the message boards. They are trying to prove that access to professional knowledge and presence in the environment that brings together caregivers can significantly improve level of performance and satisfaction. Even if the aid is granted only through an online platform of information sharing, the support effects are clearly visible.